PENINGKATAN KEMAMPUAN MENULIS TEKS FABEL DENGAN PEMBELAJARAN BERBASIS PORTOFOLIO PADA SISWA KELAS VIII SMP NEGERI 1 PONDOK KELAPA BENGKULU TENGAH - Yuliani, Santi (UNIB Press, 2016)
The purpose of this study to describe comprehensively the increase in the Ability to Write Text Fabel with Portfolio Based Learning to Students of Class VIII SMP Negeri 1 Pondok Kelapa Bengkulu Tengah. The method used is classroom action research. Sources of data obtained through eighth grade students worksheet F. Data collection techniques in this study is the testing techniques and nontes (observation, journals, and interviews). This research was conducted in three cycles. First cycle consisted of 2 meetings, the second cycle consists of two sessions, and the third cycle comprises one meetings. The test results of this study indicate that an increased ability to write text fable in students. The average value of the class in the first cycle of 63.6 (enough) with a passing rate of 27%, increased in the second cycle with an average of 70 (good) with a passing rate of 56.7%. Then increased again in the third cycle, which amounted to 76 (excellent) with a passing rate reached 86.7%.